The Behavior of Using Online System of Public Aspirations and Complaints Service (LAPOR) in Mataram City - Muhammad Iqbal; Cindy Yulita Virginia (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2020)
Public Complaint and Aspiration Service (LAPOR!) was initially a program spearheaded by the Presidential Work Unit for Development Supervision and Control (UK4). This program is associated with the administration of public services by all government agencies. Furthermore, it is used by the Mataram City Government as a medium to facilitate public aspirations and complaints. Therefore, this research aims to comprehend the factors influencing the community in applying the LAPOR! Application in the Mataram city in 2019. This is a mixed method research with data obtained from 70 user communities through interviews with related agencies and by distributing questionnaires, with the PLS and SPSS applications used for analysis. The results showed that the variable performance expectancy, effort expectancy, and social influence significantly affect behavioral intention. Meanwhile, facilitating condition and behavioral intention has a positive and significant impact on the utilization of LAPOR! Application. These were indicated by the P-value <0.005 and the T statistical value> 1.96, thereby concluding that each hypothesis proposed in this study is accepted.